1985
DOI: 10.1021/bi00325a038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the replacement of a double bond by a cyclopropane ring in phosphatidylethanolamines: a deuterium NMR study of phase transitions and molecular organization

Abstract: The thermotropic behavior and molecular properties of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE) and 1-palmitoyl-2-dihydrosterculoyl-sn-glycero-3-phosphoethanolamine (PDSPE) have been investigated by 2H NMR spectroscopy using samples selectively labeled at the 5'-, 9'-, 10'-, and 16'-positions of the sn-2 chains. Comparison with the corresponding phosphocholine analogues (POPC and PDSPC), obtained as intermediate synthetic products, was used to monitor the role of the polar head group. Replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
57
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 31 publications
15
57
0
Order By: Relevance
“…At 30 • C, the |SCH| values for the fluid fraction of the clinical-type LSE sample were determined to be 0.2 to 0.25 for the first acyl-chain carbons and decrease along the acyl chain and finally reach values close to zero for ω CH3. The |SCH| profile closely resembles previously measured SCH profiles of saturated acyl chains in the L α(d) phase (29,47,48) in model phospholipid systems with simple composition. The decrease of |SCH| from the acyl-chain carbons near the glycerol backbone to the carbons at the bilayer center relates to the different probabilities for dihedral rotations along the acyl chains.…”
Section: Resultssupporting
confidence: 83%
“…At 30 • C, the |SCH| values for the fluid fraction of the clinical-type LSE sample were determined to be 0.2 to 0.25 for the first acyl-chain carbons and decrease along the acyl chain and finally reach values close to zero for ω CH3. The |SCH| profile closely resembles previously measured SCH profiles of saturated acyl chains in the L α(d) phase (29,47,48) in model phospholipid systems with simple composition. The decrease of |SCH| from the acyl-chain carbons near the glycerol backbone to the carbons at the bilayer center relates to the different probabilities for dihedral rotations along the acyl chains.…”
Section: Resultssupporting
confidence: 83%
“…[14,34] In Sim2 and Sim3, the average area per lipid is slightly larger than experimental values, whereas the membrane thickness is thinner. We also found that the order parameters |S CD | of lipids with d min > 18 Å in Sim4 were closer to experimental values, [35][36][37] compared to those in Sim2 and Sim3 (see Supporting Information, Fig. S4).…”
Section: Consistency With Other Structural Parameters Of Lipid Bilayerssupporting
confidence: 73%
“…1 shows the raw data for the apparent specific volumes υ of mixtures of cholesterol with several different lipids as a function of cholesterol mole fraction x. For most of the samples, the pure lipid bilayers were in the fluid Lα phase, T > T M , where the chain melting temperature T M is 41.4 °C for DPPC (Nagle and Wilkinson, 1978), 24.0 °C for DMPC (Nagle and Wilkinson, 1978), 39°C for BSM (McIntosh et al, 1992), −5 °C for POPC (Perly et al, 1985) and −15.5 °C for DOPC (Webb et al, 1993). Employing the convention that the temperature will be placed in parentheses after the acronym for the lipid, these samples were DOPC(30), POPC(30), DPPC(50), DMPC(30) and BSM(45).…”
Section: Discussionmentioning
confidence: 99%